Integrating maintenance in a collaborative design method for equipments in wester Africa : cas of Burkina Faso - (:unkn) unknown (My University, 2007)
To provide food equipment to users of Western African Countries (WAC) it is required to take into account, since the phases of design, maintenance aspects as a function of specificities of the socio-technical and economic context of these countries. The proposal was elaborated using concepts from the industrial engineering developed in North-eastern countries, analysis of the traditional practices of maintenance in the food processing small scale units of Burkina Faso, and experimentation of a tool for integration of maintenance by a local team made up of designers, users and actors of maintenance. For this purpose, three tools and one approach have been proposed. The tools are: a model of analysis and representation of existing maintenance network, a specification document allowing capitalization of technical data and a set of design rules oriented maintenance as DFX tools. The approach of design oriented maintenance in the WAC allows the use of these three tools by a multi-competences team. The experimentation in Benin by a local design team showed the applicability of these tools.
Keywords: African Research